APLIKASI MIKORIZA GRANUL DAN POWDER MENGGUNAKAN TEKNIK COATING PADA JAGUNG MANIS (Zea mays L. Saccharata) DI TANAH LATOSOL DAN REGOSOL - Fahrizal Hazra; Fatimah Nur Istiqomah; Hetty Novita Agus (Jurnal Tanah dan Sumberdaya Lahan, 2022)
The demand for sweet corn increases over time. To increase sweet corn production, many farmers often use inorganic fertilizers excessively. Excessive use of inorganic fertilizers can have a negative impact on soils. One of the efforts that can be made to increase sweet corn production is the provision of biofertilizers, such as mycorrhizae. This study used a completely randomized design (CRD) with two factors. The first factor was the application of fertilizer with 7 levels of treatment, namely Control; NPK fertilizer + organic fertilizer; NPK fertilizer + organic fertilizer + 2.5 g mycorrhizal granules; NPK fertilizer + organic fertilizer + 5 g mycorrhizal granules; NPK fertilizer + organic fertilizer + 2.5 g mycorrhizal powder; NPK fertilizer + organic fertilizer + 5 g mycorrhizal powder; and NPK fertilizer + organic fertilizer + mycorrhizal powder (coating). The second factor was two different soils used as growing media, namely Regosol and Latosol from Dramaga. This study was carried out in five replications. The parameters observed were plant height, stem diameter, plant biomass, root colonization, soil available P, and total P in plants. The results showed that the application of mycorrhizal powder with coating techniques increased the growth of maize plants, the level of root colonization, the availability of soil phosphorus nutrients, and plant phosphorus uptake by the plants.